Analisis Kemampuan Pemecahan Masalah Matematika Dalam Menyelesaikan Soal Kompetitif Ditinjau Dari Kecerdasan Logis Matematis - Muhammda Faisal Khatami; Nyoman Sridana; Laila Hayati; Amrullah Amrullah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe mathematical problem-solving in terms of students solving competitive questions with Polya indicator. The research approach used is a qualitative approach to the type of quantitative research. The research subjects of class X MIPA SMAN 5 Mataram academic year 2020/2021 were selected by purposive sampling. The research subjects were 2 students with a high level of mathematical logical intelligence, 2 students with a moderate level of mathematical logical intelligence, and 2 students with a low level of mathematical logical intelligence. Data collection techniques in this study were written tests and interviews. Data analysis is performed starting from data reduction, data presentation, and then drawing conclusions. The result shows that (i) mathematical problem-solving students with high mathematical logical intelligence are able to solve the problems from each step of solving Polya correctly; (ii) mathematical problem-solving students with mathematical logical intelligence are able to meet the three Indicators of problem-solving based on Polya's steps, although it is not yet optimal; (iii) students mathematical problem-solving in terms of low mathematical logical intelligence is not able to solve problems based on Polya's steps correctly.